Correlation of compound muscle action potential generated by donor nerves with the recovery of elbow flexion in Oberlin transfer in brachial plexus injury - Thatte, Mukund Ramchandra; Raut, Binita Bharat; Hiremath, Amita Shivyogi; Nehete, Sushil Ramesh; Nayak, Nayana Somala (Indian Journal of Plastic Surgery, 2018)
Objective: To study the correlation of compound muscle action potential of donor nerves with the recovery of elbow flexion in Oberlin transfer in brachial plexus injury. Introduction: Distal nerve transfer using motor fascicle of ulnar or median nerve to restore elbow flexion is a part of reconstructive surgery after upper brachial plexus injury, first described by Oberlin et al. However, one of the most critical influences on functional outcome is number of functioning motor axons in donor fascicle which is reflected by its compound muscle action potential. We studied whether nerve transfers with donor nerves showing higher amplitudes will yield better reinnervation of muscle and therefore better function as estimated by clinical examination. Methods: We prospectively studied 30 cases of upper brachial plexus injury, of which were treated with Oberlin transfer using ulnar or median or both nerves. The prerequisites were no elbow flexion and hand and wrist flexors showing the power of more than Medical research Council MRC Grade 4. Donor nerves selected either ulnar or median having CMAP >4 mv in our electrophysiology laboratory during nerve conduction study. Patients were followed up for 1 year and assessed clinically for restoration of elbow flexion, weight tolerance. Results: A total of 30 patients of Oberlin transfer were evaluated for improvement power of biceps and elbow flexion. (MRC) grading was done at 1 year. Twenty-seven patients had a good result (MRC grade ≥3), i.e., 90% of patients. Based on the MRC grades, we categorised the patients into two groups as follows: Group A and Group B. Group A included patients with MRC Grade 4–5 and Group B included Grades 3–3.5. We tried to establish a correlation between CMAP and MRC scores by comparison of MRC grade patients for their pre CMAPs which revealed a statistically significant higher CMAPs between the groups. (Mann–Whitney U-test, P = 0.028). This indicates the association of higher pre-CMAPs with higher MRC grades. Conclusion: We conclude that higher the compound muscle action potential of donor nerves, better the recovery of elbow flexion in Oberlin transfer in brachial plexus injury.
Keywords: CMAP of donor's nerves; elbow flexion; Oberlin transfer